EU strategy for the Baltic Sea Region (BSR) in time of crisis - Kisiel-Łowczyc, Anna Barbara (Publishing House of the Wrocław University of Economics, 2009)
The Baltic, an inland, shelf sea of northern Europe – landlocked by the continent – is like a keystone of northern, eastern, central and western Europe. With narrow and relatively shallow straits, Baltic is like a lake connected with the North Sea. Such natural conditions hamper the accessibility of the Baltic Sea, also in technological terms, e.g. for maritime transport. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 228-236